A Practical Solution for 77 K Fluorescence Measurements Based on LED Excitation and CCD Array Detector - Lamb, Jacob; Forfang, Kristin; Hohmann-Marriott, Martin (PLOS ONE, 2015)
The fluorescence emission spectrum of photosynthetic microorganisms at liquid nitrogen temperature (77 K) provides important insights into the organization of the photosynthetic machinery of bacteria and eukaryotes, which cannot be observed at room temperature. Conventionally, to obtain such spectra, a large and costly table-top fluorometer is required. Recently portable, reliable, and largely maintenance-free instruments have become available that can be utilized to accomplish a wide variety of spectroscopy-based measurements in photosynthesis research. In this report, we show how to build such an instrument in order to record 77K fluorescence spectra. This instrument consists of a low power monochromatic light-emitting diode (LED), and a portable CCD array based spectrometer. The optical components are coupled together using a fiber optic cable, and a custom made housing that also supports a dewar flask. We demonstrate that this instrument facilitates the reliable determination of chlorophyll fluorescence emission spectra for the cyanobacterium Synechocystis sp. PCC 6803, and the green alga Chlamydomonas reinhardtii.